Virus-Dependent Phosphorylation of the IRF-3 Transcription Factor Regulates Nuclear Translocation, Transactivation Potential, and Proteasome-Mediated Degradation - Rongtuan Lin; Christophe Heylbroeck; Paula M. Pitha; John Hiscott (1998)
ABSTRACTThe interferon regulatory factors (IRF) consist of a growing family of related transcription proteins first identified as regulators of the alpha beta interferon (IFN-α/β) gene promoters, as well as the interferon-stimulated response element (ISRE) of some IFN-stimulated genes. IRF-3 was originally identified as a member of the IRF family based on homology with other IRF family members and on binding to the ISRE of the ISG15 promoter. IRF-3 is expressed constitutively in a variety of tissues, and the relative levels of IRF-3 mRNA do not change in virus-infected or IFN-treated cells. In the present study, we demonstrate that following Sendai virus infection, IRF-3 is posttranslationally modified by protein phosphorylation at multiple serine and threonine residues, which are located in the carboxy terminus of IRF-3. A combination of IRF-3 deletion and point mutations localized the inducible phosphorylation sites to the region -ISNSHPLSLTSDQ- between amino acids 395 and 407; point mutation of residues Ser-396 and Ser-398 eliminated virus-induced phosphorylation of IRF-3 protein, although residues Ser-402, Thr-404, and Ser-405 were also targets. Phosphorylation results in the cytoplasm-to-nucleus translocation of IRF-3, DNA binding, and increased transcriptional activation. Substitution of the Ser-Thr sites with the phosphomimetic Asp generated a constitutively active form of IRF-3 that functioned as a very strong activator of promoters containing PRDI-PRDIII or ISRE regulatory elements. Phosphorylation also appears to represent a signal for virus-mediated degradation, since the virus-induced turnover of IRF-3 was prevented by mutation of the IRF-3 Ser-Thr cluster or by proteasome inhibitors. Interestingly, virus infection resulted in the association of IRF-3 with the CREB binding protein (CBP) coactivator, as detected by coimmunoprecipitation with anti-CBP antibody, an interaction mediated by the C-terminal domains of both proteins. Mutation of residues Ser-396 and Ser-398 in IRF-3 abrogated its binding to CBP. These results are discussed in terms of a model in which virus-inducible, C-terminal phosphorylation of IRF-3 alters protein conformation to permit nuclear translocation, association with transcriptional partners, and primary activation of IFN- and IFN-responsive genes. ACKNOWLEDGMENTSWe thank Dimitris Thanos, Stephane Richard, and Illka Julkunen for reagents used in this study. We also thank members of the Molecular Oncology Group, Lady Davis Institute, for helpful discussions.This research was supported by grants from the Medical Research Council of Canada (J.H. and R.L.), the National Cancer Institute (J.H.), and the National Institutes of Health (P.M.P.). R.L. was supported in part by a Fraser Monat McPherson Fellowship from McGill University, C.H. was supported by a FRSQ/FCAR studentship, and J.H. was supported by an MRC Scientist award.